2016
DOI: 10.3390/nu8060339
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Whey, Caseinate, or Milk Protein Ingestion on Muscle Protein Synthesis after Exercise

Abstract: Whey protein (WP) is characterized as a “fast” protein and caseinate (CA) as a “slow” protein according to their digestion and absorption rates. We hypothesized that co-ingestion of milk proteins (WP and CA) may be effective for prolonging the muscle protein synthesis response compared to either protein alone. We therefore compared the effect of ingesting milk protein (MP) to either WP or CA alone on muscle protein synthesis after exercise in rats. We also compared the effects of these milk-derived proteins to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 42 publications
2
39
1
Order By: Relevance
“…The EXE/Suppl-imm and EXE/Suppl-1h groups displayed increased levels of insulin compared to the other groups, while the EXE/Suppl-imm group also had elevated levels of glucose. Kanda et al [27] visualized the peak of intramuscular and plasma leucine levels in male Sprague-Dawley rats that swam and received milk protein (whey protein and casein) at 60 min, but without significant alterations of plasma insulin concentrations. Further, Dijk et al [31] observed elevated levels of intramuscular and plasma leucine in C57/BL6RJ mice at 25 months of age after 60, 75, and 90 min of leucine-enriched whey protein gavage, but with no changes in glucose concentrations measured at 60 and 75 min.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The EXE/Suppl-imm and EXE/Suppl-1h groups displayed increased levels of insulin compared to the other groups, while the EXE/Suppl-imm group also had elevated levels of glucose. Kanda et al [27] visualized the peak of intramuscular and plasma leucine levels in male Sprague-Dawley rats that swam and received milk protein (whey protein and casein) at 60 min, but without significant alterations of plasma insulin concentrations. Further, Dijk et al [31] observed elevated levels of intramuscular and plasma leucine in C57/BL6RJ mice at 25 months of age after 60, 75, and 90 min of leucine-enriched whey protein gavage, but with no changes in glucose concentrations measured at 60 and 75 min.…”
Section: Discussionmentioning
confidence: 99%
“…Protein fractions such as whey protein (WP) and casein (CA) are found in milk. WP has a higher content of branched-chain amino acids (BCAA) and is considered a "fast" protein, while CA is considered a "slow" protein due to its structure that affects the absorption speed [27,28]. Although post-exercise protein feeding has been extensively used as a nutritional strategy by athletes [29,30], the combined effects of acute resistance exercise and protein ingestion after a fasting period on the autophagy pathway are not completely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Bovine milk proteins are of the highest quality because they possess a complete profile of essential amino acids [ 10 ], have high amino acid digestibility and absorptivity [ 11 , 12 ], and are associated with marked changes in MPS [ 13 , 14 ] through the activation of signaling of the mammalian target of rapamycin (mTOR) [ 15 ]. Furthermore, milk has the potential to be a good protein supplement over the course of a long training period [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been widely reported that the combination of cereals and legumes complement the limiting amino acids in each source [ 8 , 9 , 10 ]. Although several studies have demonstrated the effect of dietary protein, mainly casein or whey [ 11 , 12 ], on growth and protein synthesis [ 13 , 14 , 15 ], less is known about the effect of different dietary protein sources or combinations of vegetable proteins to activate liver and muscle mTORC1 (mechanistic target of rapamycin)-signaling pathway. Clinical and consumer market interest is increasingly directed toward the use of plant-based proteins as dietary components to increase protein synthesis; however, there is controversy about whether the ingestion of a plant-based diet results in lower protein synthesis compared to animal-derived proteins.…”
Section: Introductionmentioning
confidence: 99%
“…However, diets as consumed inevitably consist of mixtures of proteins, which improve the quality of the protein by complementing the limiting amino acids in each source. Most studies have assessed muscle protein synthesis after the ingestion of free amino acids, milk, whey or casein [ 12 ]. In contrast, few studies have assessed the impact of plant-based protein ingestion on mTORC1-signaling pathway involved in protein synthesis.…”
Section: Introductionmentioning
confidence: 99%